Anemia in prospective blood donors deferred by the copper sulphate technique of hemoglobin estimation. Issue 1 (December 2015) - Antwi-Baffour, Samuel; Annor, David; Adjei, Jonathan; Kyeremeh, Ransford; Kpentey, George; Kyei, Foster
Abstract Background Patients who require transfusion as part of their clinical management have the right to expect sufficient blood to be available to meet their needs and to receive the safest blood possible. Donor deferrals (disqualification) lead to loss of precious blood donors and blood units available for transfusion purposes. It is believed that a large majority of donor deferrals are due to temporal and correctable causes such as anemia in developing countries. It is therefore important to determine anemia among donor population to inform decision-making on the type of measures to be taken to reduce deferrals due to anemia. The aim of the study was to determine anemia in prospective blood donors deferred by the copper sulphate technique of hemoglobin estimation. This, to provide information that would help plan a future strategy for donor recruitment and management. Methods Three (3) ml of venous blood samples were collected from the study subjects into EDTA anticoagulant tubes. The hemoglobin levels and red cell indices were measured using Sysmex hematology analyser. A thin blood film was prepared and stained using Leishman stain and then observed under the light microscope. Results The prevalence of anemia among the total deferred patients (538) was 17.1 %. Four different types of anemia were found among the subjects. These were normocytic normochromic (46.74 %), microcytic hypochromic (42.39 %) normocytic hypochromic (8.70 %), and microcytic normochromic anemia (2.17 %). Conclusion The study showed that a significant number of the prospective blood donors deferred for having low hemoglobin by the copper sulphate method turned out to have anemia by the standard method of diagnosis. Prevalence of anemia among apparently healthy blood donors was therefore higher than expected. Measures must therefore be taken to address this in order not to lose potential blood donors due to a correctable and preventable cause such as anemia.